Revealing Obstacles to the Implementation of Diversion Against Children in Conflict with the Law - Larasati Larasati (Estudiante Law Journal, 2023)
The purpose of this study was to find out and analyze efforts to implement diversion against children who are in conflict with the law.Children who have violated the rules and are classified as criminal acts. The results of this study, researchers found thatFirst,theeffectiveness of the implementation of diversion for children who are in conflict with the law has not been effective. This is due to the lack of effort on the part of the perpetrator and the perpetrator's family in seeking diversion, the victim and the victim's family do not want to accept diversion, and the low understanding of members of the Gorontalo City Police on Diversion and the lack of welfare of police members have contributed to the process of implementing diversion to become less effective. Second, obstacles in the implementation of diversion against children in conflict with the law are caused by obstacles from the substance of the law caused by the Juvenile Criminal Court System Law itself, obstacles from the legal structure due to low and lack of human resources from the police, obstacles from the public